Effects of miR-195-5p on cell proliferation and apoptosis in gestational diabetes mellitus via targeting EZH2 - Liao, Xiaojie (Mol Med Rep, 2020)
Gestational diabetes mellitus (GDM) is a type of diabetes mellitus (DM) that occurs during pregnancy. The present study aimed to investigate the roles of microRNA (miR)-195-5p and enhancer of zeste homolog 2 (EZH2) in GDM, and their potential association. Human umbilical vein endothelial cells (HUVECs) were collected from healthy and GDM umbilical cords, and the endothelial properties were detected by flow cytometry. mRNA expression levels of miR-195-5p and EZH2, and EZH2 protein expression levels were detected by reverse transcription-quantitative PCR (RT-qPCR) and western blot analysis, respectively. Cell colony formation and flow cytometry were performed to determine cell proliferation and apoptosis. Furthermore, the target gene of miR-195-5p was predicted and assessed using a dual-luciferase reporter assay. The levels of cell viability, proliferation and apoptosis following the overexpression of miR-195-5p, EZH2 or miR-195-5p + EZH2, were detected using Cell Counting Kit-8, colony formation and flow cytometry assays, respectively. In addition, the mRNA expression levels of miR-195-59 and EZH2, and EZH2 protein expression levels following transfection with overexpression plasmids were detected using RT-qPCR and western blot analysis, respectively. It was identified that high mRNA expression of miR-195-5p, and low EZH2 mRNA and protein expression levels decreased the level of cell proliferation and the high apoptotic rate of GDM-HUVECs. In addition, miR-195-5p was predicted and identified to target EZH2, and miR-195-5p overexpression was identified to inhibit cell proliferation and promote apoptosis. However, it was demonstrated that upregulation of EZH2 could alleviate the inhibition of cell proliferation and the increased apoptotic rate induced by miR-195-5p overexpression. Therefore, the present results suggested that miR-195-5p may inhibit cell viability, proliferation and promote apoptosis by targeting EZH2 in GDM-induced HUVECs.